Current trends in and future potential of crowdfunding to finance R&D of treatments for neglected tropical diseases. Issue 7 (July 2021) - Benazzouz, Safouane M.; Malkinson, John; Tóth, Gergely
Highlights: Crowdfunding of R&D for neglected tropical diseases (NTDs) has been on the rise. Nevertheless, it has been underused and has not reached its full potential. Factors contributing positively to the success of crowdfunding were identified. The promotion of the crowdfunding ecosystem is needed to further its potential. Abstract : A serious lack of funding exists for the research and development (R&D) of therapeutics, diagnostics, and preventive measures for neglected tropical diseases (NTDs). Hence, crowdfunding to finance R&D for NTDs has high importance, because it is a new and alternate source of capital. This study explores current trends of crowdfunding for R&D for NTDs. Our study showed that, although the number of crowdfunding campaigns for NTDs has been increasing since 2010, crowdfunding overall has not reached its full potential. Several factors contributing positively to the success of crowdfunding campaigns were identified. These and the promotion of the crowdfunding ecosystem could aid the unlocking of its potential as a complementary financing source to conventional funding practices of R&D for NTDs.